Exploration of the Mediation Role of Work Engagement and Work Family Enrichment in Working Mothers - Destari Putri, N Audi; Budi Sulistyo Radikun, Tulus (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Women often face conflicts when deciding to continue working after having children. Despite making a significant contribution to the economy, many choose to quit their jobs due to role conflicts. This study aims to expand the literature on work-family relationships experienced by working mothers, focusing on the mediating role of work-family enrichment and work engagement, as well as job crafting as an antecedent. The research method uses a survey with questionnaires that include job crafting, work engagement, and work-family enrichment. This study uses data from 169 working mothers using a sampling technique in the form of convenience sampling. The data were analyzed using simple linear regression analysis to test the relationship between job crafting, work engagement, and work-family enrichment. Furthermore, a simple mediation analysis was used to test the role of mediation in work engagement and work-family enrichment. The results show the importance of job crafting in increasing work engagement and work-family enrichment. This study also explores the role of mediation in work-family enrichment and work engagement in relation to job crafting. These findings can help develop strategies and programs that support women in maintaining work engagement while considering their family roles. Perempuan sering menghadapi konflik saat memutuskan untuk terus bekerja setelah memiliki anak. Meskipun memberikan kontribusi signifikan terhadap ekonomi, banyak yang memilih berhenti kerja karena konflik peran. Penelitian ini bertujuan memperluas literatur mengenai hubungan pekerjaan dan keluarga yang dialami ibu bekerja, dengan fokus pada peran mediasi work-family enrichment dan work engagement, serta job crafting sebagai antesedennya. Metode penelitian menggunakan survei dengan kuesioner yang mencakup job crafting, work engagement, dan work-family enrichment. Penelitian ini menggunakan data dari 169 ibu bekerja dengan menggunakan teknik sampling berupa convenience sampling. Data dianalisis dengan menggunakan analisis regresi linear sederhana untuk menguji hubungan antara job crafting, work engagement, dan work-family enrichment. Selanjutnya, analisis mediasi sederhana digunakan untuk menguji peran mediasi pada work engagement dan work-family enrichment. Hasil menunjukkan pentingnya job crafting dalam meningkatkan work engagement dan work-family enrichment. Penelitian ini juga mengeksplorasi adanya peran mediasi pada work-family enrichment dan work engagement dalam hubungannya dengan job crafting. Temuan ini dapat membantu mengembangkan strategi dan program yang mendukung perempuan dalam menjaga keterlibatan kerja sambil mempertimbangkan peran keluarga mereka.